2019
DOI: 10.1111/dth.12985
|View full text |Cite
|
Sign up to set email alerts
|

Biofibre® Artificial Hair Implant : Retrospective Study on 1.518 Patients with alopecia and Present Role in Hair Surgery

Abstract: To treat alopecia, there are many surgical and nonsurgical treatments available nowadays. In the surgical one, the Biofibre® hair implantation system represents an important innovation with artificial hair with special physical, chemical, and mechanical features and the new Biofibre® Automatic device. Implant on 1,518 patients has been reported in this study where the Biofibre® hair implant technique is performed on men and women with varying degrees of baldness and for the treatment of various causes of alope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown approximately 95% to 98% satisfaction rate among patients. 1 , 2 , 4 , 5 However, 6% to 13% reported allergic, inflammatory, or infectious complications in which approximately 2% were not solved and required fiber extraction. 1 , 2 , 3 , 4 Infections are mainly caused by Staphylococci aureus and epidermidis , Streptococcus pyogenes, and corynebacterium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown approximately 95% to 98% satisfaction rate among patients. 1 , 2 , 4 , 5 However, 6% to 13% reported allergic, inflammatory, or infectious complications in which approximately 2% were not solved and required fiber extraction. 1 , 2 , 3 , 4 Infections are mainly caused by Staphylococci aureus and epidermidis , Streptococcus pyogenes, and corynebacterium.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 4 , 5 However, 6% to 13% reported allergic, inflammatory, or infectious complications in which approximately 2% were not solved and required fiber extraction. 1 , 2 , 3 , 4 Infections are mainly caused by Staphylococci aureus and epidermidis , Streptococcus pyogenes, and corynebacterium. 1 , 5 Inflammatory complications are described as mild reddening and itching, 6 histologically shown as peri-implant inflammation and folliculitis 7 and in some cases foreign body reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall complication rate has been 7.4-30% temporary superficial inflammation or infection that usually subsided within 15 days of topical cortisone and local/systemic antibiotic treatment, and 1.02-2.1% serious complications necessitating removal of implants. 3,4 In the most recent retrospective study on 1518 patients with artificial hair implant for alopecia, complications rates decreased from 20.8% in 1994 to 9.27% in 2018. 4 Synthetic hair implant reactions have been folliculitis, crusting, abscesses, granulomatous reactions and scarring.…”
Section: Dystrophic Calcinosis Of the Scalp From Artificial Hair Impl...mentioning
confidence: 99%